Factors affecting the somatic cells count in milk of Murciano-granadina goat breed: Preliminary results - Cosci F.; Ruíz F.A.; Castel J.M.; Pleguezuelos J.; Martínez F.; Gutiérrez R.; Mena Y.; Camúñez-Ruiz J. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
Somatic cell count (SCC) in milk is an indicator of the udder´s health. The National Association of Murciano-granadina Goat Breeders (CAPRIGRAN) has developed a program in order to improve the quantity and the quality of milk, being the SCC an important milk quality aspect. The aim of this study is to identify the factors significantly affecting the SCC content in milk of Murcia-granadina goats. Data from 18 farms were collected, with a total of 5799 lactations. 10 variables have been analyzed, 7 quantitative (number of births, lactation period days, drying period days, milk production per day, fat contain, protein contain and SCC) and 3 qualitative (type of system, drying treatment and milking valorization). The most influencing quantitative variables in the SCC are: milk production per day and lactation period days and the drying period days. The most influencing qualitative variables are: type of system and milking valorization. Further studies are necessary for better understanding the influence of type of system on the SCC, especially on factors related to facilities and the feeding.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)